Patient experience of scar assessment and the use of scar assessment tools during burns rehabilitation: a qualitative study. Issue 1 (1st June 2021) - Price, Kate; Moiemen, Naiem; Nice, Laura; Mathers, Jonathan
Abstract: Background: Scar assessment plays a key role during burns aftercare, to monitor scar remodelling and patients' psychosocial well-being. To aid assessment, subjective scar assessment scales are available that use health-care professionals' and patients' opinions to score scar characteristics. The subjective scales are more widely used in clinical practice over objective scar measures. To date, there is no research that considers patients' views on scar assessment and the role of subjective and objective assessment tools. Therefore, the aim of this qualitative study was to explore patients' perspectives on scar assessment and the utility of scar assessment tools during burns rehabilitation. Methods: Semi-structured interviews were conducted with 10 adult burn patients who were being reviewed in clinic for scarring. Participants were recruited via their clinical care team and research nurses at the Queen Elizabeth Hospital, Birmingham, UK. Topics covered during interview included patient experience of scar assessment, the use of scar assessment tools and discussion surrounding important factors to be addressed when assessing scars. A thematic analysis using the Framework Method was conducted. Results: Participants identified key subthemes that contribute towards the overarching theme of patient-centred scar assessment. These are: patient-led care; continuity in care; learning how to self-manage scarring; and psychological assessment. Links were demonstrated between these subthemes and the remaining themes that describe scar assessment strategies, indicating their potential patient-centred contributions. The subjective opinions of clinicians were found to be valued above the use of subjective or objective scar assessment tools. Scar assessment scales were perceived to be a beneficial method for self-reflection in relation to psychosocial functioning. However, minimal feedback and review of completed assessment scales led to uncertainty regarding their purpose. Patients perceived objective tools to be of primary use for health-care professionals, though the measures may aid patients' understanding of scar properties. Conclusions: Scar assessment tools should be used to support, rather than replace, health-care professionals' subjective judgements of scarring. Adapting the way in which clinicians introduce and use scar assessment tools, according to patient needs, can support a patient-centred approach to scar assessment.